Over the garden wall [videorecording (DVD)] (Cartoon Network, 2015)
From creator Patrick McHale, one of the minds behind Adventure Time. Cartoon Network's first every animated mini-series. It follows the story of two brothers, Greg and Wirt, who find themselves in a strange forest. Along the way, they meet a bluebird named Beatrice who helps them navigate the strange land in the hopes of making their way home.